PENELITIAN TANAH SEBAGAI PENDUKUNG PENGEMBANGAN INSTALASI PENGOLAHAN LIMBAH CAIR DOMESTIK DI KANTOR BPP TEKNOLOGI - Hernaningsih, Taty (Jurnal Air Indonesia, 2010)
Domestic wastewater from the regional office in Jakarta is one of the contributors to environmental pollution. Many office buildings in Jakarta are not managing the domestic wastewater, except BPP Technology office has managed its domestic wastewater by building domestic wastewater treatment plant. Increasing officers caused decrease performance and unsufficient capacities of WWTP. WWTP expansion is needed to address the problem of environmental pollution. The success of the development of WWTP is determined by input data (soil research data) with high accuracy, design, and construction. Number of failures of civil construction in recent years due to the use of land in excess of eksploitatif carrying capacity in general, for example, groundwater exctraction in excess can cause degradation of land, construction of road above the critical height cause sliding and high buildings construction affect to the surrounding land. The research of the soil is required for the planning of WWTP BPP Teknologi. The study was to estimate the soil carrying capacity of the soil layers that had been done by conducting experiments such as the SPT (Standard Penetration Test), Sounding and Boring. Implementation of activities include soil testing in the field and soil testing in the laboratory, physical test and mechanical test, test to determine the value of ground forces. Sondir was conducted in three locations until the impermeable soil and drilling was implemented in depth of 4,00 m.. Four tubes of soil samples consisting disturbed soil and undisturbed soil from depth of 1,5 m – 2,00 m and 3,00 m – 3,50 m were taken from drilling to be analyzed in the laboratory. Keywords: IPAL, soil sounding and boring, Cone penetration test, pemampatan tanah